Bibliometric Trends in Cultural Heritage and Film Studies: Reviving Ancestral Legacy in The Digital Age - Hasni Hasni; Hasnawi Haris; M. Yunasri Ridhoh (The Innovation of Social Studies Journal, 2025)
Cultural heritage with traditional based modern technology can be used to revive and spread ancient traditions. This study aims to analyze and find out the use of film in social studies in the world. The research method is literature review analysis with data sources from various scientific journals in the scopus database. Data analysis using the keywords TITLE-ABS-KEY ("film" AND "media" AND "cultural studies") AND PUBYEAR > 2012 AND PUBYEAR < 2023)" Scopus Database, then processed and checked using VOSviewer Program version 1.6.17. The results showed that the use of film, media and cultural studies through cultural works was modified by making films, music, oral poetry in digital media, videos, promotional media and games. It was also found that by introducing and reviving ancestral heritage such as the La Galigo manuscript originating from Bugis land, South Sulawesi, Indonesia, as Memory of the Word in the digital space, it is an effort to maintain the existence of history globally and maintain and strengthen cultural norms from extinction. This study contributes practically and theoretically to developing a diversity of literature on the issue of ancestral heritage, namely ancient manuscripts as Memory of the World, to the global community.